RWANDA, IS IT A SUCCESS STORY OR EXAGGERATED? DEVELOPMENT HISTORY - Chirwa, Masauso (European Scientific Journal, ESJ, 2015)
This study is a multi-level development history analysis of Rwanda, wherein â€œdevelopmentâ€ is defined in accordance with Amartya Senâ€™s holistic approach. It takes into account social, physical and economic variables, and considers how they impact individualsâ€™ capacity to live freely. The objectives of the paper are: 1) to investigate how global, regional, national and local events have interplayed to shape the development process over time in Rwanda, 2) to discover Rwandaâ€™s unique contribution to present day development discussions, and 3) to see how development should best proceed in Rwanda today. The study was quantitative in nature. Through a brief historical survey, six key turning points have been identified as critical to Rwandaâ€™s development history: 1) the adoption of identity cards in 1926, 2) the Hutu Revolution of 1959, 3) independence from Belgium in 1962, 4) the coffee crisis of 1987-1989 and resultant SAPs, 5) the 1994 genocide, and 6) the new constitution in 2003. These turning points have helped us to understand Rwandaâ€™s development in six areas more clearly. These areas are: economic considerations, agriculture and land scarcity, gender, education, good governance and the reconciliation process. We have chosen these areas over others due to their prominence in literature surrounding Rwandan development. Despite being portrayed as a success story, the developmental situation in Rwanda is falling short in some areas. The profound structural transformation, which needs to occur in both economic and societal terms, makes future development success uncertain.